The Effect Of Self-Hypnosis Training On Improving The Ability To Concentrate And Emotions Of South Sulawesi Archery Athletes - Islam, Nur; Nawir, Nukhrawi; Hakim, Himad; Hudain, Muh. Adnan; Sahabuddin, Sahabuddin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study is an experimental study with a quantitative approach that aims to analyse the effect of self-hypnosis training on improving concentration and emotional management skills in archery athletes in South Sulawesi Province. The method used in this study is a one-group pre-test post-test design experiment, with a total sampling technique, involving 10 athletes as respondents. The research process was carried out for two months, starting from the initial observation stage, implementation of the intervention, to the final evaluation. Self-hypnosis training was given in a structured and systematic manner during the research period, with the aim of improving the mental focus and emotional stability of athletes in facing competition pressure. The research instruments used included a concentration test and a validated emotional control questionnaire. The data obtained were analysed using a t-test (paired sample t-test) to determine significant differences between the pre-test and post-test results. The results of the statistical analysis showed that there was a significant effect of self-hypnosis training on improving athletes' concentration and emotional abilities. The observation t value of 12.0000 is smaller than the t table value of 19.3000, and the significance level of 0.000 is smaller than the value of α = 0.05. This finding indicates that self-hypnosis training can significantly help athletes improve the quality of focus and emotional control during training and matches. It can be concluded that self-hypnosis training is an effective method to be applied in athlete psychological development programs, especially in sports that require high concentration, such as archery.